Genetics and Breeding of Lupinus mutabilis: An Emerging Protein Crop - Gulisano, Agata; Alves, Sofia; Martins, João Neves; Trindade, Luisa M. (Frontiers in Plant Science, 2019)
Protein crops have gained increasing interest in recent years, as a transition towards plant-protein based diets appears pivotal to ensure global food security and preserve the environment. The Andean species Lupinus mutabilis emerges as an ideal protein crop with great potential for Europe and other regions with temperate climates. This species is characterized by an oil and protein content similar to soybean and is highly valued for its adaptability to colder climates and low input agriculture on marginal land. However, its introduction outside the Andes has yet to take off. To date, L. mutabilis remains an under-studied crop, lacking high yield, early maturity and a consistent breeding history. This review paper identifies L. mutabilis limitations and potential uses, and suggests the main breeding targets for further improvement of this crop. It also highlights the potential of new molecular tools and available germplasm resources that can now be used to establish L. mutabilis as a viable protein crop.